Oxygen-Dependent Gene Expression in Development and Cancer: Lessons Learned from the Wilms’ Tumor Gene, WT1 - Scholz, Holger; Kirschner, Karin M. (Frontiers in Molecular Neuroscience, 2011)
Adequate tissue oxygenation is a prerequisite for normal development of the embryo. Most fetal organs are exquisitely susceptible to hypoxia which occurs when the delivery of oxygen is exceeded by the actual demand. Developmental abnormalities due to insufficient supply with oxygen can result from the impaired expression of genes with essential functions during embryogenesis. As such, the Wilms’ tumor gene, WT1, is among the fetal genes that are regulated by the local oxygen tension. WT1 was originally discovered as a tumor suppressor gene owing to loss-of-function mutations in a subset of pediatric renal neoplasias, known as nephroblastomas or Wilms’ tumors. Wilms’ tumors can arise when pluripotent progenitor cells in the embryonic kidney continue to proliferate rather than differentiating to glomeruli and tubules. WT1 encodes a zinc finger protein, of which multiple isoforms exist due to alternative mRNA splicing in addition to translational and post-translational modifications. While some WT1 isoforms function as transcription factors, other WT1 proteins are presumably involved in post-transcriptional mRNA processing. However, the role of WT1 reaches far beyond that of a tumor suppressor as homozygous disruption of Wt1 in mice caused embryonic lethality with a failure of normal development of the kidneys, gonads, heart, and other tissues. WT1 mutations in humans are associated with malformation of the genitourinary system. A common paradigm of WT1 expressing cells is their capacity to switch between a mesenchymal and epithelial state. Thus, WT1 likely acts as a master switch that enables cells to undergo reciprocal epithelial-to-mesenchymal transition. Impairment of renal precursor cells to differentiate along the epithelial lineage due to WT1 mutations may favor malignant tumor growth. This article shall provide a concise review of the function of WT1 in development and disease with special consideration of its regulation by molecular oxygen.